2016
DOI: 10.1590/0001-3765201620140676
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomy and ontogeny of the underground system of Chrysolaena simplex (Less.) Dematt. (Asteraceae)

Abstract: The occurrence of thickened underground systems in Asteraceae is widely reported in the literature. Given the great complexity of underground systems, which may originate from roots, stems, or both, morphoanatomical analyses are essential to ensure the use of correct terminology. The goals of this study were to describe the morpho-anatomy and ontogeny, investigate the occurrence of secondary metabolites and evaluate the effects of seasonality on the underground system of Chrysolaena simplex (Less.) Dematt. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Anatomical studies performed on 'candeia' roots confirmed the great capacity of root blossom emission in species belonging to the family Asteraceae (Appezzato-da-Glória et al, 2008). Several authors have attributed this regrowth ability to the presence of fructan-type inulin crystals in the root cells (Assega and Carvalho, 2004;Assega et al, 2011;Santos et al, 2016;Silva et al, 2015). The occurrence of crystals on the walls of the vessel elements of the secondary xylem ( Figure 2F-G) is in accordance with what Tertuliano and Figueiredo-Ribeiro (1993) described for other species of the Asteraceae family.…”
Section: Anatomical Analysesmentioning
confidence: 87%
See 1 more Smart Citation
“…Anatomical studies performed on 'candeia' roots confirmed the great capacity of root blossom emission in species belonging to the family Asteraceae (Appezzato-da-Glória et al, 2008). Several authors have attributed this regrowth ability to the presence of fructan-type inulin crystals in the root cells (Assega and Carvalho, 2004;Assega et al, 2011;Santos et al, 2016;Silva et al, 2015). The occurrence of crystals on the walls of the vessel elements of the secondary xylem ( Figure 2F-G) is in accordance with what Tertuliano and Figueiredo-Ribeiro (1993) described for other species of the Asteraceae family.…”
Section: Anatomical Analysesmentioning
confidence: 87%
“…Morvan-Bertrand et al (2001) reported a decline in the content of this carbohydrate in the leaf base of Lolium perene L. in the process of elongation, which was accompanied by a peak in the activity of the fructan enzyme: exohydroxylase in the growth zone, shortly after defoliation, suggesting the fructan as the source of carbon responsible for sustaining growth resumption. Santos et al (2016) reported seasonal variation in the amount and location of crystal accumulation in Chrysolaena simplex (Less.) Dematt.…”
Section: Anatomical Analysesmentioning
confidence: 99%
“…Cristais estão presentes nos coléteres de 35 das 108 espécies de Psychotria (Rubiaceae) dos neotrópicos, mas são raros entre as 188 espécies do resto do mundo (Lersten, 1974a (Rizzini & Heringer, 1961;Paviani, 1974;Milanez & Moraes-Dallaqua, 2003;Vilhalva & Appezzatoda-Glória, 2006b;Silva et al, 2015), e não no parênquima amilífero típico de raízes e caules tuberosos. Várias plantas de Cerrado acumulam em seus sistemas subterrâneos carboidratos, tais como amido e frutano, sendo que essas reservas são prontamente utilizadas na produção de gemas, permitindo o rebrotamento de órgãos aéreos perdidos durante a ação do fogo ou seca prolongada (Sajo & Menezes, 1986;Figueiredo-Ribeiro et al, 1991;Tertuliano & Figueiredo-Ribeiro, 1993;Hayashi & Appezzato-da-Glória, 2005;Vilhalva & Appezzato-da-Glória, 2006a, 2006bSilva et al, 2015;Santos et al, 2016).…”
Section: As Amostras Armazenadas Em Etanol 70%unclassified